Instructional Materials Enhancing High School Learners’ Engagement in Research Skills - Robinson Valenzona (Research Synergy Foundation, 2026)
Instructional Materials (IMs) were used in teaching Qualitative Research. The importance of it is undeniably as it assisted the learners in gaining knowledge. Hence, this paper employed a descriptive correlational method with the application of statistical tools in analyzing the findings. The researcher made a self-administered survey questionnaire which was distributed to the teachers who handled Qualitative Research under the Division of Science City of Muñoz, Nueva Ecija through Google form. There was a total of 19 teachers who served as participants of the study. Most of them came from Muñoz National High School (Main) – Senior High School, belonging to early adulthood with 6-10 years in service, and mostly Teacher III. They use Google Meet/Classroom and self-paced learning modules in teaching qualitative research with their laptops as their common gadget. The findings revealed that audio-visual materials, video lessons, learning activity sheets, and worksheets were the top chosen IMs used by teachers in teaching Qualitative Research. It was found out that there was a significant relationship between the profile of the respondents, particularly their age, in the use of IMs. In addition, there was a correlation between the integration of instructional materials and the topics in teaching Qualitative Research. This research recommended a guide in teaching Practical Research I wherein the identified IMs are aligned with the Most Essential Learning Competencies (MELCS)provided by the Department of Education (DepEd).